Gestão da diversidade sexual nas organizações: um estudo de caso em uma empresa de marketing digital - Chieregato, Igor de Castro (Universidade Federal de São Carlos, 2023)
The topic of cultural diversity has been evolving in recent years and gaining relevance within organizations, which have begun to see it as an opportunity when well managed. Sexual diversity management is dedicated to promote an environment that is inclusive and respectful for individuals who deviate from the cis-heteronormative hegemonic standard. This study aims to analyze the practices of sexual diversity management observed in a digital marketing company and evaluate its level of maturity based on a conceptual model. To achieve this, interviews were conducted with the company's employees n order to map the practices, as well as the analysis of historical data related to the composition of the workforce to understand how these practices have been reflected in the company's reality. The company was classified according to the pillars proposed in the conceptual model, allowing for an understanding of he current level of maturity and the main challenges to achieve the next levels.
Management of sexual diversity in organizations: a case study in a digital marketing company
Keywords: Gestão da diversidade sexual; Diversidade sexual; Marketing digital; Sexual diversity management; Sexual diversity; Digital marketing; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO